RELATIVE IRRITANT PROPERTIES OF THE CHLORINE GROUP OF ANTISEPTICS - Cullen, Glenn E. (The Rockefeller University Press, 1918)
1. The use of the ears of rabbits is proposed in testing the irritant effect of antiseptics. 2. It is necessary, because of individual variations, to use solutions having definite irritant actions as controls. 3. 0.5 per cent sodium hypochlorite solutions have minimum irritant effects over a range of alkalinity of from about 100 to 1,000 times that of water (pH about 9 to 10). Solutions may be adjusted within these limits by use of the end-points of powdered phenolphthalein, of alcoholic solutions of either o-cresolphthalein or phenolphthalein. 4. Sodium hypochlorite solutions kept within the above range of alkalinity by either borate or carbonate buffer salts, i.e. Dakin's solution, show the same irritative properties whether made from bleaching powder and sodium carbonate, or from chlorine and sodium carbonate. 5. Electrolytically prepared solutions of the same concentration have similar irritant action. 6. Solutions, however, that have an alkalinity less than that indicated by the end-point of alcoholic phenolphthalein solutions (pH of 8.5 to 8.8) or greater than that indicated by the end-point to powdered phenolphthalein (pH of 10.2) are intensely irritating. 7. 0.5 per cent sodium hypochlorite solution from which most of the calcium has been precipitated and calcium hypochlorite solution of equivalent hypochlorite concentration are only slightly irritating. 8. 2 per cent chloramine-T solution has no irritant action. 9. 5 per cent dichloramine-T in chlorcosane and chlorcosane alone irritate rabbit ears to a slight degree only.